CSF1R-Mediated Myeloid Cell Depletion Prolongs Lifespan But Aggravates Distinct Motor Symptoms in a Model of Multiple System Atrophy - Battis, Kristina; Florio, Jazmin B.; Mante, Michael; Lana, Addison; Naumann, Isabel; Gauer, Carina; Lambrecht, Vera; Müller, Sarina Katrin; Cobo, Isidoro; Fixsen, Bethany; Kim, Ha Yeon; Masliah, Eliezer; et al. (Journal of Neuroscience, 2022)
As the CNS-resident macrophages and member of the myeloid lineage, microglia fulfill manifold functions important for brain development and homeostasis. In the context of neurodegenerative diseases, they have been implicated in degenerative and regenerative processes. The discovery of distinct activation patterns, including increased phagocytosis, indicated a damaging role of myeloid cells in multiple system atrophy (MSA), a devastating, rapidly progressing atypical parkinsonian disorder. Here, we analyzed the gene expression profile of microglia in a mouse model of MSA (MBP29-ha-syn) and identified a disease-associated expression profile and upregulation of the colony-stimulating factor 1 (Csf1). Thus, we hypothesized that CSF1 receptor-mediated depletion of myeloid cells using PLX5622 modifies the disease progression and neuropathological phenotype in this mouse model. Intriguingly, sex-balanced analysis of myeloid cell depletion in MBP29-ha-syn mice revealed a two-faced outcome comprising an improved survival rate accompanied by a delayed onset of neurological symptoms in contrast to severely impaired motor functions. Furthermore, PLX5622 reversed gene expression profiles related to myeloid cell activation but reduced gene expression associated with transsynaptic signaling and signal release. While transcriptional changes were accompanied by a reduction of dopaminergic neurons in the SNpc, striatal neuritic density was increased upon myeloid cell depletion in MBP29-ha-syn mice. Together, our findings provide insight into the complex, two-faced role of myeloid cells in the context of MSA emphasizing the importance to carefully balance the beneficial and adverse effects of CSF1R inhibition in different models of neurodegenerative disorders before its clinical translation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: colony-stimulating factor 1 receptor; motor function; multiple system atrophy; myeloid cells; neuron-micro-glia interaction; PLX5622